2022
DOI: 10.3390/plants11172198
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Changes of Arabica Coffee under Different Intensities and Durations of Water Stress in the Brazilian Cerrado

Abstract: Coffee farmers have faced problems due to drought periods, with irrigation being necessary. In this sense, this study aimed to evaluate the responses to different levels and durations of water deficit in arabica coffee genotypes in the Cerrado region. The experiment consisted of three Coffea arabica genotypes and five water regimes: full irrigation (FI 100 and FI 50—full irrigation with 100% and 50% replacement of evapotranspiration, respectively), water deficit (WD 100 and WD 50—water deficit from June to Sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 31 publications
3
10
0
Order By: Relevance
“…In addition, these plants had reduced productivity compared to irrigated treatments. Thus, the plants in the present study preserved a higher moisture content (60 %) in their tissues than those evaluated by Silva et al (2022) (50 %) although all of them have gone through periods of scarcity of rain and high temperatures. Almeida et al (2018) also evaluated the RWC of 23 genotypes of C. arabica in the field during the dry season.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…In addition, these plants had reduced productivity compared to irrigated treatments. Thus, the plants in the present study preserved a higher moisture content (60 %) in their tissues than those evaluated by Silva et al (2022) (50 %) although all of them have gone through periods of scarcity of rain and high temperatures. Almeida et al (2018) also evaluated the RWC of 23 genotypes of C. arabica in the field during the dry season.…”
Section: Discussionmentioning
confidence: 49%
“…This aspect is reinforced by the observation that the lack of rain associated with temperatures above 28 o C tend to harm the different phenological stages of the coffee plant (Thomaziello, 2000;Ávila et al, 2011Ávila et al, , Noctor et al, 2014. On the other hand, Silva et al (2022) found that plants in the field of genotypes E237, Catuaí Vermelho and IAPAR 59 under water deficit had RWC lower than 50% in two consecutive years, with 2019 being characterized by greater scarcity of rain- fall and higher temperatures than in 2020. In addition, these plants had reduced productivity compared to irrigated treatments.…”
Section: Discussionmentioning
confidence: 96%
“…Historically, the breeding process was guided by searching low height, structurally compact, and productive cultivars (Guerreiro-Filho et al, 2018). So, insensitivity of orthotropic height in Iapar 59, Catuaí 99, and wild 'E027' indicated one morphological characteristic that is stable in cultivars and not decisive to coffee breeding (Silva et al, 2022). On the other hand, even mild drought (Fig.…”
Section: At Plant Scale: Orthotropic Axis and Branching Ordersmentioning
confidence: 99%
“…Therefore, irrigation is highly recommended for great part of coffee areas in Brazil, as rainfed conditions negatively impact plant growth traits, such are relative growth rate or leaf area (Dias et al, 2007;Souza et al, 2016), but no differences are observed in the number of leaves or number of 2 nd order branches due to irrigation (Chemura, 2014). C. arabica genotypes show reduction in physiological and productive traits when cultivated under rainfed compared to irrigated conditions in Brazilian Cerrado, a very dry environment, with Iapar 59 cultivar highlighted as the most productive and a wild Ethiopia accession 'E237' as the less productive one (Silva et al, 2022). As a perennial crop, coffee plants exposed to multiple drought cycles can express differential acclimation capabilities, associated with their defense mechanisms, allowing them to be maintained in a 'state of alert' to successfully deal with new drought events (Menezes- Silva et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation